Immune potentiating and antitoxic effects of camel milk against cyclophosphamide-induced toxicity in BALB/C mice - Khan, Masood Alam (International Journal of Health Sciences, 2017)
Objective: Cyclophosphamide (CYP), a cytotoxic anticancer drug, causes a substantial reduction in leukocytes numbers, called leukopenia. Leukopenia is a major predisposing factor to infections caused by opportunistic pathogens. The aim of the present study is to assess the effects of camel milk consumption against CYP-induced leukopenia and other toxic effects. Materials and Methods: CYP at a dose of 250 mg/kg was injected in the mice through the intraperitoneal route. Each mouse was orally administered with 1 ml of camel milk twice daily for 10 days. The blood was taken from various groups of mice to determine quantitative and qualitative changes in the leukocytes. The protective role of camel milk against CYP-induced toxicity was also assessed by determining the levels of antioxidant enzymes, superoxide dismutase (SOD), and catalase (CAT) in the hepatic tissue homogenates. Results: Mice injected with CYP showed substantial weight loss and a simultaneous depletion of leukocytes. Oral administration of camel milk protected mice against CYP-induced toxicity. The group of CYP-injected mice that received camel milk showed lesser decrease in their weight and leukocyte numbers. CYP-injected mice showed lower levels of SOD and CAT, whereas simultaneous consumption of camel milk resulted in lesser decrease in the levels of SOD and CAT in liver homogenates. Conclusions: The results of the present study suggest that camel milk may have an immunopotentiating role in diseases or conditions associated with leukopenia- or drug-induced toxicities.